Era digital dalam perkembangan perpustakaan: Digitalisasi perpustakaan - Laraswati, Sinthia Dwi (Maliki Interdisciplinary Journal, 2024)
This paper discusses the digital era in the development of public libraries. The presence of a new era in the current library, makes the library must adapt its development to follow the existing era. In the previous era, libraries were conventional in all aspects, such as collections and management. In today’s digital era, libraries are required to use technology in the activities in it. Library transformation in following technological developments is marked by the existence of digital libraries. The digital library is an evolution of the conventional library in which it contains printed collections, which then evolve into digitalized collections. With the change in the collection which was originally printed and then digitized, of course, the technology that is in it is certainly not spared. Information technology has contributed to the development of libraries which were previously conventional libraries to become digital libraries. The involvement of information technology in the creation of digital libraries indicates that libraries are following developments in the digital era. With the implementation of information technology in the library, creating a new dimension in searching for information in the library can be accessed quickly. Therefore, in this writing, we will discuss how the digital era is in the development of libraries with the digitization of libraries. Keywords: digital era, digital library, information technology